The impact of inclusive leadership styles on employees’ job satisfaction: a study in UiTM Cawangan Sarawak Kampus Samarahan 1 & 2 / Celine Ujang and Monica Nilam Andrew - Ujang, Celine; Andrew, Monica Nilam (2024)
The aim of this research is to examine how leadership styles that emphasize inclusion affect employee job satisfaction at UiTM Cawangan Sarawak Kampus Samarahan 1 & 2. The study includes a thorough investigation of demographic profiles, a reliability pilot test, and an in- depth analysis of the main findings, such as the level ofjob satisfaction, gender differences, and the association between inclusive leadership and employee satisfaction. The results show a high and consistent level of job satisfaction among employees, regardless of gender. Importantly, inclusive leadership, which involves openness, accessibility, and availability, shows a positive relationship with job satisfaction. The study suggests leadership training programs, continuous monitoring, and proposes directions for future research to improve organizational strategies. Despite limitations, the research adds to the knowledge of the vital role of inclusive leadership in creating a positive work environment. The findings help organizations in enhancing employee satisfaction through inclusive leadership practices.